Konstruksi Hukum Pidana terhadap Tindak Pidana Plagiarisme Karya Tulis - Muhammad Maulani; Rini Apriyani; Ine Ventyrina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Plagiarism in scientific writing is a serious violation that not only harms the original creator but also undermines academic integrity, the development of scientific knowledge, and the credibility of educational institutions. This research aims to analyze the regulation of plagiarism acts based on the laws and regulations in Indonesia, as well as to build a firmer criminal law construction against acts of plagiarism within academic settings. This study employs a normative juridical method with a doctrinal approach, examining relevant laws and legal theories. The findings indicate that although plagiarism has been regulated in several legal instruments such as the Indonesian Penal Code (KUHP), Law Number 28 of 2014 on Copyright, Law Number 20 of 2003 on the National Education System, and the Regulation of the Minister of National Education Number 17 of 2010, the existing regulations tend to be administrative in nature and have not provided a sufficient deterrent effect. Therefore, a more comprehensive and implementable criminal law construction is needed to ensure the protection of scientific works and legal certainty in the enforcement of criminal sanctions against perpetrators of plagiarism. In addition, preventive efforts through academic ethics education, the implementation of plagiarism detection systems, and the strengthening of internal policies within universities are also important steps that must be optimized.